A Comparative Legal Analysis of Chile and Argentina in the Global Energy Transition - Rodriguez-Granillo, Guillermo; Brener, Maria Bleichmar; Navarro, Pedro Ortúzar (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2026)
The global transition toward renewable energy has significantly increased the demand for lithium, a critical mineral essential for battery technologies used in electric vehicles and energy storage systems. As two major lithium-producing countries in South America, Chile and Argentina play a strategic role in the global supply chain for energy transition technologies. However, lithium extraction activities have raised growing concerns regarding environmental sustainability, water scarcity, and the rights of indigenous communities living in high-altitude salt flat ecosystems. This study examines how legal frameworks governing lithium extraction incorporate principles of environmental justice and public participation. Using a normative juridical and comparative legal approach, this research analyzes statutory regulations, environmental governance mechanisms, and policy frameworks in Chile and Argentina. The study finds three main issues. First, lithium governance regimes in both countries are primarily oriented toward economic development and strategic resource policy rather than environmental justice considerations. Second, while both countries formally recognize indigenous consultation mechanisms, the implementation of participatory governance remains limited in practice. Third, environmental governance institutions face structural challenges in addressing cumulative ecological impacts in fragile salt flat ecosystems. Comparative analysis shows that Chile has developed stronger institutional oversight and environmental regulatory mechanisms, whereas Argentina adopts a more decentralized governance structure that places greater authority at the provincial level. These differences produce varying degrees of environmental accountability and community participation in lithium governance. This research argues that strengthening environmental justice principles and participatory governance mechanisms is essential to ensure that the global energy transition does not create new forms of environmental inequality in lithium-producing regions.